K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 8 2022

12 = 3.2.2

25 = 5.5

để có chung là gì ? 2.2.3.5.5

 

22 tháng 8 2020

\(A=\frac{7}{10.11}+\frac{7}{11.12}+\frac{7}{12.13}+...+\frac{7}{69.70}\)

\(A=7\left(\frac{1}{10.11}+\frac{1}{11.12}+\frac{1}{12.13}+....+\frac{1}{69.70}\right)\)

\(A=7\left(\frac{1}{10}-\frac{1}{11}+\frac{1}{11}-\frac{1}{12}+....+\frac{1}{69}-\frac{1}{70}\right)\)

\(A=7\left(\frac{1}{10}-\frac{1}{70}\right)\)

\(A=7\cdot\frac{3}{35}=\frac{21}{35}\)

22 tháng 8 2020

\(A=\frac{7}{10\cdot11}+\frac{7}{11\cdot12}+\frac{7}{12\cdot13}+...+\frac{7}{69\cdot70}\)

\(A=7\left(\frac{1}{10\cdot11}+\frac{1}{11\cdot12}+\frac{1}{12\cdot13}+...+\frac{1}{69\cdot70}\right)\)

\(A=7\left(\frac{1}{10}-\frac{1}{11}+\frac{1}{11}-\frac{1}{12}+...+\frac{1}{69}-\frac{1}{70}\right)\)

\(A=7\left(\frac{1}{10}-\frac{1}{70}\right)=7\cdot\frac{3}{35}=\frac{3}{5}\)

\(B=\frac{1}{25\cdot27}+\frac{1}{27\cdot29}+\frac{1}{29\cdot31}+...+\frac{1}{73\cdot75}\)

\(B=\frac{1}{2}\left(\frac{2}{25\cdot27}+\frac{2}{27\cdot29}+\frac{2}{29\cdot31}+...+\frac{2}{73\cdot75}\right)\)

\(B=\frac{1}{2}\left(\frac{1}{25}-\frac{1}{27}+\frac{1}{27}-\frac{1}{29}+...+\frac{1}{73}-\frac{1}{75}\right)\)

\(B=\frac{1}{2}\left(\frac{1}{25}-\frac{1}{75}\right)=\frac{1}{2}\cdot\frac{2}{75}=\frac{1}{75}\)

\(C=\frac{4}{2\cdot4}+\frac{4}{4\cdot6}+\frac{4}{6\cdot8}+...+\frac{4}{2008\cdot2010}\)

\(C=\frac{4}{2}\left(\frac{2}{2\cdot4}+\frac{2}{4\cdot6}+\frac{2}{6\cdot8}+...+\frac{2}{2008\cdot2010}\right)\)

\(C=2\left(\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{6}+...+\frac{1}{2008}-\frac{1}{2010}\right)\)

\(C=2\left(\frac{1}{2}-\frac{1}{2010}\right)=2\cdot\frac{502}{1005}=\frac{1004}{1005}\)

8 tháng 2 2017

a) x - (17 - 8) = 5 + (10 - 3x)

x - 17 + 8 = 5 + 10 - 3x

x + 3x = 5 + 10 + 17 - 8

4x = 24

x = 24 : 4

x = 6

b) 25 - (30 + x) = x - (27 - 8)

25 - 30 - x = x - 27 + 8

-x - x = -27 + 8 - 25 + 30

-2x = -14

x = (-14) : (-2)

x = 7

c) (x - 12) - 15 = (20 - 7) - (18 + x)

x - 12 - 15 = 20 - 7 -18 - x

x + x = 20 - 7 - 18 + 12 + 15

2x = 22

x = 22 : 2

x = 11

d) 9 - 25 = (7 - x) - (25 + 7)

9 - 25 = 7 - x - 25 - 7

x = 7 - 25 - 7 - 9 +25

x = -9

9 tháng 1 2016

10) 37.(27+25)-27.(37+25)=37.27+37.25-27.37-27.25

=37.25-27.25=25(37-27)=25.10=250

11)3.(-5+3)+7(2+5)=3.(-2)+7.7=-6+49=43

12)-3.(2-7)-6(8-5)=-3.(-5)-6.3=15-18=-3

9 tháng 1 2016

      

10 tháng 5 2016

5/8<8/11

7/9>5/8

12/18=18/27

25/36>25/63

9 tháng 8 2017

a) \(\dfrac{7}{-25}+\dfrac{8}{25}=\dfrac{-7}{25}+\dfrac{8}{25}=\dfrac{1}{25}\)

\(\dfrac{4}{5}+\dfrac{4}{-18}=\dfrac{4}{5+\left(-18\right)}=\dfrac{4}{-13}=\dfrac{-4}{13}\)

\(\dfrac{7}{21}+\dfrac{9}{-36}=\dfrac{1}{3}+\dfrac{1}{-4}=\dfrac{1}{3+\left(-4\right)}=\dfrac{1}{-1}=1\)

b) \(\dfrac{12}{20}-\dfrac{2}{5}=\dfrac{12}{20}+\left(\dfrac{-2}{5}\right)=\dfrac{3}{5}+\dfrac{-2}{5}=\dfrac{3+\left(-2\right)}{5}=\dfrac{1}{5}\)

\(\dfrac{2}{3}-\dfrac{-5}{6}=\dfrac{2}{3}+\dfrac{5}{6}=\dfrac{4}{6}+\dfrac{5}{6}=\dfrac{9}{6}=\dfrac{3}{2}\)

\(6-\dfrac{3}{20}=6+\dfrac{-3}{20}=\dfrac{60}{60}+\dfrac{-9}{60}=\dfrac{51}{60}\)

c) \(\dfrac{2}{21}.\dfrac{-7}{3}=\dfrac{2.\left(-1\right)}{7.3}=\dfrac{-2}{21}\)

\(\dfrac{27}{28}.\left(-21\right)=\dfrac{27.\left(-21\right)}{28}=\dfrac{-567}{28}\)

\(\dfrac{-15}{7}.\dfrac{-14}{25}=\dfrac{-3.\left(-2\right)}{1.5}=\dfrac{6}{5}\)

18 tháng 5 2019
https://i.imgur.com/Qmwoqb8.jpg
18 tháng 5 2019
https://i.imgur.com/muAG8nx.jpg
1 tháng 2 2016

minhmoi hoc lop 5 thui

1 tháng 2 2016

a)2100
b)64
c)700

19 tháng 1 2024

Bài 1:

a; \(\dfrac{5}{18}\) + \(\dfrac{8}{19}\) - \(\dfrac{7}{21}\) + (- \(\dfrac{10}{36}\) + \(\dfrac{11}{19}\)  + \(\dfrac{1}{3}\)) - \(\dfrac{5}{8}\)

=  \(\dfrac{5}{18}\) + \(\dfrac{8}{19}\) - \(\dfrac{1}{3}\) -\(\dfrac{10}{36}\) + \(\dfrac{11}{19}\) + \(\dfrac{1}{3}\) - \(\dfrac{5}{8}\)

= (\(\dfrac{5}{18}\) - \(\dfrac{10}{36}\)) + (\(\dfrac{8}{19}\) + \(\dfrac{11}{19}\)) - (\(\dfrac{1}{3}\) - \(\dfrac{1}{3}\)) - \(\dfrac{5}{8}\)

= (\(\dfrac{5}{18}\) - \(\dfrac{5}{18}\)) + \(\dfrac{19}{19}\) - 0 - \(\dfrac{5}{8}\)

= 0 + 1 - \(\dfrac{5}{8}\)

\(\dfrac{3}{8}\)

b; \(\dfrac{1}{13}\) + (\(\dfrac{-5}{18}\) - \(\dfrac{1}{13}\) + \(\dfrac{12}{17}\)) - (\(\dfrac{12}{17}\) - \(\dfrac{5}{18}\) + \(\dfrac{7}{5}\))

\(\dfrac{1}{13}\) - \(\dfrac{5}{18}\) - \(\dfrac{1}{13}\) + \(\dfrac{12}{17}\) - \(\dfrac{12}{17}\) + \(\dfrac{5}{18}\) - \(\dfrac{7}{5}\)

= (\(\dfrac{1}{13}\) - \(\dfrac{1}{13}\)) + (\(\dfrac{12}{17}\) - \(\dfrac{12}{17}\)) + (-\(\dfrac{5}{18}\) + \(\dfrac{5}{18}\)) - \(\dfrac{7}{5}\)

= 0 + 0 + 0 - \(\dfrac{7}{5}\)

= - \(\dfrac{7}{5}\)

19 tháng 1 2024

Bài 1 c;

   \(\dfrac{15}{14}\) - (\(\dfrac{17}{23}\) - \(\dfrac{80}{87}\) + \(\dfrac{5}{4}\)) + (\(\dfrac{17}{23}\) - \(\dfrac{15}{14}\) + \(\dfrac{1}{4}\))

=  \(\dfrac{15}{14}\) - \(\dfrac{17}{23}\) + \(\dfrac{80}{87}\) - \(\dfrac{5}{4}\) + \(\dfrac{17}{23}\) - \(\dfrac{15}{14}\) + \(\dfrac{1}{4}\)

= (\(\dfrac{15}{14}-\dfrac{15}{14}\)) + (\(-\dfrac{17}{23}+\dfrac{17}{23}\)) - (\(\dfrac{5}{4}\) - \(\dfrac{1}{4}\)) + \(\dfrac{80}{87}\)

= 0 + 0 - 1 + \(\dfrac{80}{87}\)

= - \(\dfrac{7}{87}\)